Dysfunctional mucociliary clearance in asthma and airway remodeling - New insights into an old topic - Jesenak, Milos; Durdik, Peter; Oppova, Dasa; Franova, Sona; Diamant, Zuzana; Golebski, Kornel; Banovcin, Peter; Vojtkova, Jarmila; Novakova, Elena (Respiratory medicine, 2023)
Bronchial asthma is a heterogeneous respiratory condition characterized by chronic airway inflammation, airway hyperresponsiveness and airway structural changes (known as remodeling). The clinical symptoms can be evoked by (non)specific triggers, and their intensity varies over time. In the past, treatment was mainly focusing on symptoms' alleviation; in contrast modern treatment strategies target the underlying inflammation, even during asymptomatic periods. Components of airway remodeling include epithelial cell shedding and dysfunction, goblet cell hyperplasia, subepithelial matrix protein deposition, fibrosis, neoangiogenesis, airway smooth muscle cell hypertrophy and hyperplasia. Among the other important, and frequently forgotten aspects of airway remodeling, also loss of epithelial barrier integrity, immune defects in anti-infectious defence and mucociliary clearance (MCC) dysfunction should be pointed out. Mucociliary clearance represents one of the most important defence airway mechanisms. Several studies in asthmatics demonstrated various dysfunctions in MCC - e.g., ciliated cells displaying intracellular disorientation, abnormal cilia and cytoplasmic blebs. Moreover, excessive mucus production and persistent cough are one of the well-recognized features of severe asthma and are also associated with defects in MCC. Damaged airway epithelium and impaired function of the ciliary cells leads to MCC dysfunction resulting in higher susceptibility to infection and inflammation. Therefore, new strategies aimed on restoring the remodeling changes and MCC dysfunction could present a new therapeutic approach for the management of asthma and other chronic respiratory diseases.
Keywords: remodelace dýchacích cest; Mucociliary Clearance; mukociliární clearance; Chronic inflammation; Airway defence mechanisms; Mucociliary clearance; hyperplazie; Asthma; bronchiální astma; Humans; Inflammation; Airway Remodeling; lidé; Hyperplasia; Airway remodeling; Epithelial dysfunction; Bronchial asthma; zánět